Perancangan Sistem Informasi Akademik pada MI Adipati Sindurejo Jumo - Khasanah, Ilfi Laili; Kapti, Kapti; Fatkhurrochman, Fatkhurrochman (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The design of the Academic Information System at MI Adipati Sindurejo Jumo aims to facilitate the process of managing student academic data including master data, teacher data, subject data, academic year data, class data, and UKS networking data. In modeling and visualizing the system, use the data flow diagram (DFD) model. The academic information system at MI Adipate Juma is a web-based information system developed using the PHP and MYSQL programming languages. Next, the system is tested using the black box testing method and user evaluation. User evaluation was carried out on 30 respondents consisting of school principals, teachers, students and UKS officers. The results of the user evaluation show that the impact and use value of implementing the system is of good value as shown by the evaluation percentage based on the likers scale of 78.67%.